2015
DOI: 10.1093/cercor/bhv219
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Connectivity Develops Rapidly Around Term Age and Changes Between Vigilance States in the Human Newborn

Abstract: Large-scale coupling in neuronal activity is essential in all cognitive functions, but its emergence and functional correlates are poorly known in the human newborn. This study aimed to characterize functional connectivity in the healthy human newborn, and to identify the changes in connectivity related to vigilance states and to maturation during the early postnatal weeks. We recorded active and quiet sleep of 38 sleeping newborn babies using multichannel electroencephalography (EEG) at 2 neonatal time points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 69 publications
5
67
0
Order By: Relevance
“…Koolen et al showed that the synchrony between cortical activations in QS periods, based on the ‘Activation Synchrony Index’ (ASI), significantly increased between 30 and 40 weeks PMA [5,79]. Tokariev et al provided a benchmarking study that functional brain connectivity develops rapidly and is related to vigilance states in human term neonates [84]. All together, these studies provide important developmental features of functional brain maturation related to sleep states, however, current procedures for automated sleep detection, which allow subsequent quantification, are limited.…”
Section: Automated Sleep-eeg Analysismentioning
confidence: 99%
“…Koolen et al showed that the synchrony between cortical activations in QS periods, based on the ‘Activation Synchrony Index’ (ASI), significantly increased between 30 and 40 weeks PMA [5,79]. Tokariev et al provided a benchmarking study that functional brain connectivity develops rapidly and is related to vigilance states in human term neonates [84]. All together, these studies provide important developmental features of functional brain maturation related to sleep states, however, current procedures for automated sleep detection, which allow subsequent quantification, are limited.…”
Section: Automated Sleep-eeg Analysismentioning
confidence: 99%
“…This bimodality is thought to govern early functional brain wiring and diminishes with advancing postnatal age, when young neurons mature and endogenous brain activity (SATs) is progressively replaced by sensory driven oscillations (ongoing cortical activity) (Omidvarnia et al, 2014). Other prominent features of neonatal brain activity encompass distinct differences between sleep states, well before the onset of mature sleep-wake EEG representations and highly dynamic signature patterns of functional neural synchrony that mature rapidly during the first few postnatal weeks (Tokariev et al, 2015).…”
Section: Electrophysiological Connectivitymentioning
confidence: 99%
“…Still, studies on infancy and early childhood, a period when the brain is highly plastic and shows significant structural and functional developmental changes, have not been conducted. Only one study examined PAC during infancy: PAC recorded during sleep decreased over the first two weeks after birth (Tokariev et al, 2016).…”
Section: Introductionmentioning
confidence: 99%